Molecular damage and responses of oral keratinocyte to hydrogen peroxide - Kuan-Yu Lin; Ching-Hung Chung; Jheng-Sian Ciou; Pei-Fang Su; Pei-Wen Wang; Dar-Bin Shieh; Tzu-Chueh Wang (BMC, 2019)
Abstract Background Hydrogen peroxide (H2O2)-based tooth bleaching reagents have recently increased in popularity and controversy. H2O2 gel (3%) is used in a Nightguard for vital bleaching; transient tooth sensitivity and oral mucosa irritation have been reported. Genotoxicity and carcinogenicity have also been significant concerns. Methods We used primary cultured normal human oral keratinocytes (NHOKs) as an in vitro model to investigate the pathological effects to mitochondria functions on human oral keratinocytes exposed to different doses of H2O2 for different durations. Results An MTT assay showed compromised cell viability at a dose over 5 mM. The treatments induced nuclear DNA damage, measured using a single-cell gel electrophoresis assay. A real-time quantitative polymerase chain reaction showed H2O2 induced significant increase in mitochondrial 4977-bp deletion. Mitochondrial membrane potential and apoptosis assays suggested that oxidative damage defense mechanisms were activated after prolonged exposure to H2O2. Reduced intracellular glutathione was an effective defense against oxidative damage from 5 mM of H2O2. Conclusion Our study suggests the importance for keratinocyte damage of the dose and the duration of the exposure to H2O2 in at-home-bleaching. A treatment dose ≥100 mM directly causes severe cytotoxicity with as little as 15 min of exposure.